Pragmatics of space - Jucker, Andreas H.; Hausendorf, Heiko (Handbooks of pragmatics, 2022)
This handbook provides a comprehensive overview of spatial configurations of language use and of language use in space. It consists of four parts. The first part covers the various practices of describing space through language, including spatial references in spoken interaction or in written texts, the description of motion events as well as the creation of imaginative spaces in storytelling. The second part surveys aspects of the spatial organization of face-to-face communication including not only spatial arrangements of small groups in interaction but also the spatial dimension of sign language and gestures. The third part is devoted to the communicative resources of constructed spaces and the ways in which these facilitate and shape communication. Part four, finally, is devoted to pragmatics across space and cultures, i.e. the ways in which language use differs across language varieties, languages and cultures.